FINANCIAL BEHAVIOR OF GENERATION Z IN POLAND - Sobolewska, Katarzyna (Management and Administration Journal, 2025)
The article addresses the subject of personal finances, focusing on the financial behaviors of Generation Z – a generation entering the period of economic activity, in Poland. The author defines finances as a system of processes related to the accumulation and expenditure of funds in various segments of the economy. In particular, the importance of personal finances is emphasized as an area important for individuals and households. Financial behaviors are understood as the actions of individuals related to financial management, including, among others, saving, investing, spending, indebtedness and financial planning. Their shape is determined by psychological, social, cultural and economic factors. The article cites definitions of the concept from the literature on the subject, emphasizing its interdisciplinary nature and importance for contemporary scientific research. The author points to changes in financial paradigms caused by globalization, technological progress and dynamic socio-economic changes, which have a particular impact on young generations. Generation Z, entering the labor market, must face new challenges, such as high inflation, job uncertainty and difficult access to credit, which requires them to have developed financial competences. The aim of the article is to identify and analyze financial attitudes and the level of economic knowledge among Polish Generation Z representatives. Particular attention is paid to the impact of economic education on financial decisions, saving practices, investing and the issue of debt. The article is based on a critical analysis of literature and data from reports on selected aspects of financial behavior.